A Pharmacological and Therapeutic Plant Review of Bhallataka (Semecarpus Anacardium) in Classical and Modern Medicine - D. Mohan Kumar; Ch. Sri Durga (International Journal of Ayurveda and Pharma Research, 2025)
Bhallataka (Semecarpus anacardium Linn.), commonly known as the marking nut tree, is a widely utilized medicinal plant in Ayurveda, recognized for its diverse pharmacological activities. Classical Ayurvedic texts such as Charaka Samhita, Sushruta Samhita, Ashtanga Hridaya, and various Nighantus extensively document its properties, formulations, and therapeutic indications. It is classified under Upavisha (semi-poisonous drugs), requiring meticulous purification (Shodhana) before internal use. Various parts of the plant-particularly the seed, kernel (Majja), fruit, and oil-exhibit actions such as Deepana, Pachana, Krimighna, Shukrala, Rasayana, and Kaphavatahara. These properties make Bhallataka valuable in treating conditions like Kushtha (skin disorders), Arsha (piles), Grahani (IBS), Gulma (abdominal masses), Pandu (anaemia), and Vatarakta (gout). Modern pharmacological research has corroborated many classical claims, demonstrating its anti-inflammatory, immunomodulatory, antimicrobial, antioxidant, and anticancer effects. Phytochemical investigations reveal bioactive constituents like bhilawanol, semecarpol, anacardol, and biflavonoids responsible for its therapeutic efficacy. Despite its efficacy, improper handling may cause severe toxic reactions; hence, traditional antidotes and dietary guidelines (Pathya-Apathya) are crucial during administration. This review compiles comprehensive information from classical and contemporary sources to present a holistic understanding of Bhallataka-from its botanical description, purification techniques, therapeutic actions, and formulations to modern evidence-based validations highlighting its integrative significance in traditional and modern medicine.